Highly adhesive polyester film

The polyester film with an adhesive layer composed of polyester resin, polyvinyl alcohol resin, and a nitrogen-containing crosslinking agent addresses adhesion issues with hydrophilic and photocurable adhesives, ensuring effective adhesion and blocking resistance without organotin catalysts, suitable for optical applications.

JP7605110B2Active Publication Date: 2024-12-24TOYOBO CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021533903
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-07-23
Filing Date
2020-07-02
Publication Date
2024-12-24
Estimated Expiration
2040-07-02

AI Technical Summary

Technical Problem

Conventional polyester films used as polarizer protective films in liquid crystal displays face issues with adhesion to both hydrophilic adhesives and photocurable adhesives, particularly when exposed to temperature and humidity variations, leading to blocking problems due to dew condensation, and the use of organotin catalysts is environmentally harmful.

Method used

A polyester film with an easily adhesive layer formed by a composition containing polyester resin, polyvinyl alcohol resin, and a crosslinking agent with a nitrogen element, which does not include organic tin, ensuring excellent adhesion to both hydrophilic and photocurable adhesives while being environmentally friendly.

Benefits of technology

The solution provides a polyester film with enhanced adhesion properties to hydrophilic and photocurable adhesives, resistant to blocking under varying environmental conditions, and avoids the use of harmful organotin catalysts, making it suitable for optical applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605110000001
    Figure 0007605110000001
  • Figure 0007605110000002
    Figure 0007605110000002
  • Figure 0007605110000003
    Figure 0007605110000003
Patent Text Reader

Abstract

The invention addresses the problem of providing a readily adherable polyester film containing substantially no organotin compound as a cross-linking / curing catalyst within a composition forming a readily adhering layer, and demonstrating excellent tight-adhesion to both hydrophilic adhesives and photo-curable adhesives. The polyester film has a readily adhering layer on at least one surface thereof. The readily adhering layer is yielded by curing a composition comprising a polyester-based resin, a polyvinyl alcohol-based resin, and a cross-linking agent having a nitrogen element. The readily adherable polyester film contains substantially no organotin as a curing catalyst for the composition in the readily adhering layer. On the readily adhering layer surface, the content percentage of the nitrogen element among the elements constituting the surface is between 2.0 at% and 3.0 at% inclusive as analyzed by ESCA (electron spectroscopy for chemical analysis).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an easily adhesive polyester film that exhibits excellent adhesion to both hydrophilic adhesives and photocurable adhesives for bonding a polarizer and a polarizer protective film, for example. The easily adhesive polyester film of the present invention is suitable as a base film for optical members such as displays, and is particularly suitable as a polarizer protective film. [Background technology]

[0002] In a liquid crystal display device, polarizing plates are arranged on both sides of a glass substrate that forms the surface of a liquid crystal panel due to its image forming method. Conventional polarizing plates generally have a structure in which a polarizer protective film is attached to both sides of a polarizer made of a polyvinyl alcohol-based film and a dichroic material such as iodine via a hydrophilic adhesive such as a polyvinyl alcohol-based resin. As a protective film used to protect a polarizer, a triacetyl cellulose film has been used in the past from the viewpoint of optical properties and transparency.

[0003] However, triacetyl cellulose does not have sufficient durability, and when a polarizing plate using a triacetyl cellulose film as a polarizer protective film is used under high temperature or high humidity, the performance of the polarizing plate, such as the polarization degree and hue, may be reduced. In addition, in recent years, there has been a demand for thinner polarizing plates to accommodate thinner displays, but there is a limit to how thin a triacetyl cellulose film can be made from the viewpoint of maintaining moisture barrier properties. Therefore, it has been proposed to use a polyester film as a polarizer protective film having durability and moisture barrier properties (for example, see Patent Document 1).

[0004] The triacetyl cellulose film used as a polarizer protective film has an extremely high affinity with a hydrophilic adhesive, since the surface of the film is subjected to an alkali treatment or the like. Therefore, a protective film made of a triacetyl cellulose film has an extremely high adhesion to a polarizer coated with a hydrophilic adhesive. However, the adhesion of a polyester film to a hydrophilic adhesive is insufficient, and this tendency is particularly pronounced in the case of a polyester film having orientation due to a stretching treatment. Therefore, in order to improve the adhesion to a polarizer or a hydrophilic adhesive coated on a polarizer, a surface coating of a highly hydrophilic material such as an easy-adhesion layer disclosed in Patent Document 1 has been performed on the polyester film.

[0005] Polyester films have low affinity to water, and this tendency is particularly prominent in polyester films having aromatic dicarboxylic acids as dicarboxylic acid components. In addition, polyester films having crystal orientation due to stretching have even lower affinity to water. On the other hand, polarizers and adhesives applied to polarizers generally contain polyvinyl alcohol resin as a main component and have high hydrophilicity. Due to such differences in properties, materials with high hydrophilicity, such as those used in the easy-adhesion layer disclosed in Patent Document 1, have been used as a means for firmly adhering a polyester film to a polarizer or a polyvinyl alcohol resin layer such as an adhesive applied to a polarizer.

[0006] However, when the hydrophilicity of the adhesive layer is increased, especially during transport of the film roll in winter, when the film roll is transported between indoors and outdoors in a factory, etc., condensation water adheres to the film roll due to the difference in temperature between the indoor temperature and the outdoor temperature, and blocking problems occur in which the film surface and its adhesive layer stick to each other. This is different from the blocking that occurs under pressure after being left in air containing normal water vapor, and occurs only through liquid water. In other words, it is necessary to increase the hydrophilicity in order to increase the adhesion to the adhesive, but on the other hand, blocking occurs due to condensation water, so it is extremely difficult to achieve both adhesion and blocking. Seasoning is an effective way to avoid this, but it cannot be completely avoided, and the problem is that the addition of a seasoning process delays processing and leads to a deterioration in productivity.

[0007] Recently, an adhesive (photocurable adhesive) made of a composition containing an active energy ray curable compound has been proposed as an adhesive for bonding a polarizer and a polarizer protective film. Specifically, the photocurable adhesive compound is an adhesive made of a composition containing an epoxy resin or a urethane resin as a main component and a photocationic polymerization initiator, and is cured by cationic polymerization caused by irradiation with active energy rays. Photocurable adhesives are cured by simply irradiating active energy rays, which allows for improved productivity and has been widely used in recent years (see, for example, Patent Document 2). The easy-adhesion layer of the film is required to be compatible not only with hydrophilic adhesives but also with photocurable adhesives.

[0008] Furthermore, from the viewpoint of durability of the easy-adhesion layer, an organotin catalyst is often used as a raw material to accelerate the crosslinking reaction (hardening of the easy-adhesion layer) of the easy-adhesion layer. In many documents describing conventional coating solutions containing polyvinyl alcohol, polyester, and isocyanate crosslinking agents, there is no mention of the inclusion of a crosslinking / hardening catalyst, but even without the mention, it has been commonly used. However, organotin is highly toxic and is known to affect living organisms even in small amounts, so the use of organotin compounds has been restricted in recent years. In addition, the use of organotin catalysts has a tendency to reduce the adhesion between the photocurable adhesive and the easy-adhesion layer. It is presumed that this is because the organotin catalyst reduces the activity of the photocation catalyst. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2013-063610 A [Patent Document 2] JP 2004-245925 A Summary of the Invention [Problem to be solved by the invention]

[0010] Under these circumstances, an object of the present invention is to provide an easily adhesive polyester film that is substantially free of organotin compounds as crosslinking / curing catalysts in the composition that forms the easily adhesive layer, and that has excellent adhesion to both hydrophilic adhesives and photocurable adhesives. [Means for solving the problem]

[0011] The present inventors have conducted extensive research to achieve the above object and have completed the present invention. 1. A polyester film having an easy-adhesion layer on at least one side, the easy-adhesion layer being formed by curing a composition containing a polyester resin, a polyvinyl alcohol resin, and a crosslinking agent having a nitrogen element, the easy-adhesion layer being substantially free of organotin as a curing catalyst for the composition, and the content of nitrogen elements among the surface constituent elements on the surface of the easy-adhesion layer as analyzed by ESCA (X-ray photoelectron spectroscopy) is 2.0 at% or more and 3.0 at% or less. 2. The highly adhesive polyester film as described in 1 above, wherein the peel strength of the highly adhesive layer after adhesion with water is 2 N / cm or less. 3. The highly adhesive polyester film according to the above 1 or 2, which is used as a polarizer protective film. Effect of the Invention

[0012] The present invention makes it possible to provide an easily adhesive polyester film that has excellent adhesion to both hydrophilic adhesives and photocurable adhesives, is environmentally friendly because it does not use an organotin catalyst, and can be suitably used in optical applications. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] (Polyester film) The polyester film used as the substrate in the present invention is a film mainly composed of polyester resin. Here, "a film mainly composed of polyester resin" means a film formed from a resin composition containing 50% by mass or more of polyester resin. When blended with other polymers, it means that the polyester resin is contained in an amount of 50% by mass or more, and when copolymerized with other monomers, it means that the polyester structural unit is contained in an amount of 50 mol% or more. Preferably, the polyester film contains 90% by mass or more of polyester resin, more preferably 95% by mass or more, and even more preferably 100% by mass.

[0014] The polyester resin material is not particularly limited, but a copolymer formed by polycondensation of a dicarboxylic acid component and a diol component, or a blend resin thereof can be used. Examples of dicarboxylic acid components include terephthalic acid, isophthalic acid, orthophthalic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, diphenylcarboxylic acid, diphenoxyethanedicarboxylic acid, diphenylsulfonecarboxylic acid, anthracenedicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, hexahydroterephthalic acid, hexahydroisophthalic acid, malonic acid, dimethylmalonic acid, succinic acid, 3,3-diethylsuccinic acid, glutaric acid, 2,2-dimethylglutaric acid, adipic acid, 2-methyladipic acid, trimethyladipic acid, pimelic acid, azelaic acid, dimer acid, sebacic acid, suberic acid, and dodecadicarboxylic acid.

[0015] Examples of diol components constituting the polyester resin include ethylene glycol, propylene glycol, hexamethylene glycol, neopentyl glycol, 1,2-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, decamethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexadiol, 2,2-bis(4-hydroxyphenyl)propane, and bis(4-hydroxyphenyl)sulfone.

[0016] The polyester resin may be made of one or more dicarboxylic acid components and diol components. In addition, other acid components such as trimellitic acid and other hydroxyl group components such as trimethylolpropane may be appropriately added.

[0017] Specific examples of polyester resins include polyethylene terephthalate, polypropylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate, and among these, polyethylene terephthalate is preferred in terms of the balance between physical properties and cost. In addition, in order to control optical properties such as polarization, it is also a preferred embodiment to contain other copolymerization components or other polymers. In terms of controlling the optical properties of the polyester film, preferred copolymerization components include diethylene glycol and copolymerization components having norbornene in the side chain.

[0018] When the polyester film of the present invention is used as a protective film for a polarizer, it is preferable that the film of the present invention has high transparency. The transparency of the film of the present invention is preferably such that the total light transmittance is 85% or more, more preferably 87% or more, even more preferably 88% or more, even more preferably 89% or more, and particularly preferably 90% or more. The haze is preferably 3% or less, more preferably 2.5% or less, even more preferably 2% or less, and particularly preferably 1.5% or less.

[0019] In order to improve the handling properties of the polyester film, such as slipperiness and windability, in some cases inactive particles are contained in the film, but in order to maintain high transparency, it is preferable that the content of inactive particles in the film is as small as possible. Therefore, it is preferable to have a multi-layer structure in which particles are contained only in the surface layer of the film, or to have the film substantially free of particles and to contain fine particles only in the coating layer laminated on at least one side of the polyester film.

[0020] Incidentally, "substantially free of particles" means, for example, in the case of inorganic particles, that the content is 50 ppm or less, preferably 10 ppm or less, and most preferably below the detection limit when elements derived from the particles are quantitatively analyzed by fluorescent X-ray analysis. This is because even if particles are not intentionally added to the base film, contaminants derived from foreign matter or dirt attached to the raw material resin or the line or equipment in the film manufacturing process may peel off and be inevitably mixed into the film.

[0021] Furthermore, when the polyester film has a multi-layer structure, a two-kind three-layer structure in which the inner layer contains substantially no inert particles and only the outermost layer contains inert particles is preferred, as this makes it possible to achieve both transparency and processability.

[0022] In the present invention, the thickness of the polyester film is not particularly limited, but when the polarizing plate is thinned to make the display thinner, the thickness of the film is preferably 200 μm or less, more preferably 100 μm or less, while from the viewpoint of maintaining the mechanical strength as a protective film, the thickness of the film is preferably 10 μm or more, more preferably 12 μm or more, and even more preferably 20 μm or more.

[0023] The polyester film serving as the substrate may be a single layer or a laminate of two or more layers. In addition, various additives may be contained in the film as necessary within the range in which the effects of the present invention are obtained. Examples of additives include antioxidants, light resistance agents, gelation inhibitors, organic wetting agents, antistatic agents, ultraviolet absorbers, and surfactants. When the film has a laminated structure, it is also preferable to contain additives according to the function of each layer as necessary. For example, it is also a preferred embodiment to add an ultraviolet absorber to the inner layer in order to prevent photodegradation of the polarizer.

[0024] The polyester film can be produced according to a conventional method. For example, the polyester resin is melt-extruded into a film shape, and cooled and solidified on a casting drum to form a film. As the polyester film in the present invention, either a non-stretched film or a stretched film can be used, but a stretched film is preferable from the viewpoint of durability such as mechanical strength and chemical resistance. When the polyester film is a stretched film, the stretching method is not particularly limited, and a longitudinal uniaxial stretching method, a transverse uniaxial stretching method, a longitudinal and transverse sequential biaxial stretching method, a longitudinal and transverse simultaneous biaxial stretching method, etc. can be adopted. When stretching the polyester film, the stretching may be performed before laminating the easy-adhesion layer described later, or after laminating the easy-adhesion layer. It is also possible to uniaxially stretch the polyester film in the longitudinal or transverse direction before laminating the easy-adhesion layer, and then stretch the polyester film in the other direction after laminating the coating layer.

[0025] (Easy adhesion layer) In order to improve adhesion between the polyester film in the present invention and a polarizer and a polyvinyl alcohol-based resin layer such as a hydrophilic adhesive provided on one or both sides of the polarizer, it is preferable that an easy-adhesion layer formed from a resin composition containing a polyester resin, a polyvinyl alcohol-based resin, and a crosslinking agent having a nitrogen element is laminated on at least one side of the polyester film. The easy-adhesion layer may be provided on both sides of the polyester film, or may be provided on only one side of the polyester film, with a different type of resin coating layer provided on the other side.

[0026] Without being bound by theory, it is believed that by combining a polyester resin, a polyvinyl alcohol resin, and a crosslinking agent having a nitrogen element, the polyester resin and the polyvinyl alcohol resin form separate domain units in the easy-adhesion layer, forming a phase-separated structure generally referred to as a sea-island structure. By adopting such a domain-unit separation structure, it is believed that two functions, namely, the adhesiveness to the polyester film by the domain formed by the polyester resin and the adhesiveness to the polyvinyl alcohol resin layer by the domain formed by the polyvinyl alcohol resin, are suitably achieved without impairing each other. It is believed that the crosslinking agent having a nitrogen element crosslinks the polyvinyl alcohol resin, thereby promoting and maintaining the formation of the domain structure. In addition, it is believed that the nitrogen element in the crosslinking agent easily forms hydrogen bonds with hydrophilic groups of urethane resin or epoxy resin, which are the main components of the compound of the photocurable adhesive, and therefore further improves the adhesiveness.

[0027] The components of the adhesive layer will be described in detail below.

[0028] (Polyester resin) The polyester resin used in the easy-adhesion layer in the present invention is a copolymer obtained by polycondensation of a dicarboxylic acid component and a diol component, and the dicarboxylic acid component and the diol component can be the materials of the polyester film as the substrate. From the viewpoint of improving the adhesion to the polyester film substrate, it is preferable to use a dicarboxylic acid component having the same or similar structure and properties as the dicarboxylic acid component in the polyester film as the substrate as the dicarboxylic acid component of the polyester resin. Therefore, for example, when an aromatic dicarboxylic acid is adopted as the dicarboxylic acid component of the polyester film, it is preferable to use an aromatic dicarboxylic acid as the dicarboxylic acid component of the polyester resin. As such an aromatic dicarboxylic acid component, benzenedicarboxylic acid or naphthalenedicarboxylic acid is most preferable. These are preferably used in a range of 50% or more, more preferably 60 mol% or more, and even more preferably 70 mol% with respect to the total dicarboxylic acid components. These aromatic dicarboxylic acids may be used alone or in combination of two or more. In addition to these aromatic dicarboxylic acids, aliphatic or alicyclic dicarboxylic acids, or a small amount of tricarboxylic acid may be used in combination.

[0029] The glycol component of the polyester resin is not particularly limited, and various glycols based on ethylene glycol can be used. Examples of linear glycols include ethylene glycol, diethylene glycol, triethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol.

[0030] Examples of branched glycols include 2,2-dimethyl-1,3-propanediol, 2-methyl-2-ethyl-1,3-propanediol, 2-methyl-2-butyl-1,3-propanediol, 2-methyl-2-propyl-1,3-propanediol, 2-methyl-2-isopropyl-1,3-propanediol, 2-methyl-2-n-hexyl-1,3-propanediol, 2,2-diethyl-1,3-propanediol, 2-ethyl-2-n-butyl-1,3-propanediol, 2-ethyl-2-n-hexyl-1,3-propanediol, 2,2-di-n-butyl-1,3-propanediol, 2-n-butyl-2-propyl-1,3-propanediol, and 2,2-di-n-hexyl-1,3-propanediol. Examples of cyclic glycols include cyclopentanediol, cyclohexanediol, cycloheptanediol, cyclohexanedimethanol, cycloheptanedimethanol, etc. Examples of aromatic diols include benzenedimethanol, naphthalenedimethanol, alkylene oxide adducts of bisphenol A or bisphenol fluorene, etc.

[0031] The polyester resin used in the present invention is preferably a water-soluble or water-dispersible resin in terms of compatibility with the polyvinyl alcohol resin. In order to make the polyester resin water-soluble or water-dispersible, it is preferable to copolymerize a compound containing a hydrophilic group such as a sulfonate group or a carboxylate group. Among them, a dicarboxylic acid component having a sulfonate group is suitable from the viewpoint of imparting hydrophilicity while maintaining the acid value of the polyester resin (A) low and controlling the reactivity with the crosslinking agent. Examples of the dicarboxylic acid component having a sulfonate group include sulfoterephthalic acid, 5-sulfoisophthalic acid, 4-sulfonaphthaleneisophthalic acid-2,7-dicarboxylic acid, and 5-(4-sulfophenoxy)isophthalic acid or an alkali metal salt thereof, and among them, 5-sulfoisophthalic acid is preferred. The dicarboxylic acid component having a sulfonate group is preferably 1 to 15 mol %, more preferably 1.5 to 10 mol %, and even more preferably 2 to 5 mol % of the dicarboxylic acid component of the polyester resin (A). When the amount of the dicarboxylic acid component having a sulfonate group is equal to or more than the lower limit, it is suitable for making the polyester resin water-soluble or water-dispersible, whereas when the amount of the dicarboxylic acid component having a sulfonate group is equal to or less than the upper limit, it is suitable for improving adhesion to polyester films.

[0032] The polyester resin preferably has fewer carboxylic acid groups reactive with a crosslinking agent having a nitrogen element. By reducing the number of carboxyl groups reactive with a crosslinking agent, the reactivity with the crosslinking agent may be reduced. As a result, it is considered that the polyester resin does not completely mix with the polyvinyl alcohol resin and can maintain the domain structure formed by the crosslinked polyvinyl alcohol resin. From this viewpoint, the acid value of the polyester resin is preferably 20 mgKOH / g or less, more preferably 15 mgKOH / g or less, even more preferably 10 mgKOH / g or less, particularly preferably 8 mgKOH / g or less, and most preferably 5 mgKOH / g or less. The acid value of the polyester resin can be theoretically determined from the results of component analysis by titration method or NMR, which will be described later.

[0033] In order to control the acid value of the polyester resin within the above range, it is preferable to reduce the amount of carboxylate group introduced for water solubility or water dispersion, to adopt a hydrophilic group other than carboxylate group, or to lower the carboxylate terminal concentration of the polyester resin. As a method for lowering the carboxylate terminal concentration of the polyester resin, it is preferable to adopt a polyester resin in which the carboxylate terminal group is terminally modified, or to adopt a polyester resin having a large number average molecular weight. For this reason, the number average molecular weight of the polyester resin is preferably 5000 or more, more preferably 6000 or more, and even more preferably 10000 or more. In addition, it is preferable to lower the content of an acid component having three or more carboxyl groups as a constituent of the polyester resin.

[0034] The glass transition temperature of the polyester resin is not particularly limited, but is preferably 20 to 140° C., and more preferably 30 to 130° C. If the glass transition temperature is equal to or higher than the lower limit, blocking resistance is favorable, and if the glass transition temperature is equal to or lower than the upper limit, adhesion to polyester films is favorable.

[0035] When the total solid content of the polyester resin, polyvinyl alcohol resin and nitrogen-containing crosslinking agent in the coating liquid is 100% by mass, the lower limit of the content of the polyester resin is preferably 25% by mass (in the solid content), more preferably 40% by mass, even more preferably 50% by mass, and particularly preferably 60% by mass. When the content of the polyester resin is 25% by mass or more, blocking is unlikely to occur even if water adheres to the film or the easy-adhesion layer, and there is no risk of the peel strength increasing. On the other hand, the upper limit of the polyester resin content is preferably 95% by mass, more preferably 93% by mass, even more preferably 90% by mass, and particularly preferably 85% by mass. When the content of the polyester resin is 95% by mass or less, the adhesion to the polarizer, the polyvinyl alcohol resin such as the hydrophilic adhesive, and the urethane resin of the photocurable adhesive is good, and blocking is unlikely to occur even if water adheres to the film or the easy-adhesion layer, and there is no risk of the peel strength increasing, which is preferable.

[0036] (Polyvinyl alcohol resin) The polyvinyl alcohol resin is not particularly limited, but examples thereof include polyvinyl alcohol obtained by saponifying polyvinyl acetate; derivatives thereof; saponified copolymers of vinyl acetate and monomers copolymerizable therewith; modified polyvinyl alcohol obtained by acetalization, urethane-ification, etherification, grafting, phosphorylation, etc. of polyvinyl alcohol; and the like. Examples of the monomer include unsaturated carboxylic acids and esters thereof, such as maleic acid (anhydride), fumaric acid, crotonic acid, itaconic acid, and (meth)acrylic acid; α-olefins, such as ethylene and propylene; (meth)allylsulfonic acid (soda), sodium sulfonate (monoalkyl maleate), sodium disulfonate alkyl maleate, N-methylol acrylamide, alkali salts of acrylamido alkyl sulfonates, N-vinyl pyrrolidone, and N-vinyl pyrrolidone derivatives. These polyvinyl alcohol resins may be used alone or in combination of two or more.

[0037] Examples of the polyvinyl alcohol resin used in the present invention include vinyl alcohol-vinyl acetate copolymer, vinyl alcohol-vinyl butyral copolymer, and ethylene-vinyl alcohol copolymer, and among these, vinyl alcohol-vinyl acetate copolymer and ethylene-vinyl alcohol copolymer are preferred. The degree of polymerization of the polyvinyl alcohol resin is not particularly limited, but from the viewpoint of the viscosity of the coating liquid, it is preferred that the degree of polymerization is 3000 or less.

[0038] The copolymerization ratio of vinyl alcohol is expressed by the saponification degree. The saponification degree of the polyvinyl alcohol resin of the present invention is preferably 60 mol% or more and 90 mol% or less, more preferably 65 mol% or more and 83 mol% or less, even more preferably 68 mol% or more and 80 mol% or less, even more preferably 70 mol% or more and less than 80 mol%, even more preferably 71 mol% or more and 78 mol% or less, and particularly preferably 73 mol% or more and 75 mol% or less. If the saponification degree of the polyvinyl alcohol resin is 60 mol% or more, it is preferable because it can more suitably form a crosslinked structure with a crosslinking agent having a nitrogen element. In addition, if the saponification degree of the polyvinyl alcohol resin is 90 mol% or less, it is preferable because it can more suitably exhibit compatibility with a polyester resin. The saponification degree of the vinyl alcohol resin can be determined by the alkali consumption required for hydrolysis of copolymerization units such as vinyl acetate or composition analysis by NMR.

[0039] When the total solid content of the polyester resin, polyvinyl alcohol resin and nitrogen-containing crosslinking agent in the coating solution is 100% by mass, the lower limit of the content of the polyvinyl alcohol resin is preferably 1% by mass (in the solid content), more preferably 5% by mass, even more preferably 10% by mass, particularly preferably 15% by mass, and most preferably 20% by mass. When the content of the polyvinyl alcohol resin is 1% by mass or more, the adhesion to the polyvinyl alcohol resin of the polarizer or hydrophilic adhesive, and the urethane resin of the photocurable adhesive is good, and even if water adheres to the film, blocking is unlikely to occur and there is no risk of the peel strength increasing, which is preferable. The upper limit of the content of the polyvinyl alcohol resin is preferably 65% ​​by mass, more preferably 55% by mass, even more preferably 50% by mass, particularly preferably 45% by mass, and most preferably 40% by mass. When the content of the polyvinyl alcohol resin is 65% by mass or less, even if water adheres to the film, blocking is unlikely to occur and there is no risk of the peel strength increasing, which is preferable.

[0040] (Cross-linking agent having nitrogen element) In the present invention, the nitrogen-containing crosslinking agent used in the formation of the coating layer is preferably used to strengthen the coating layer and impart stable adhesion and easy releasability when water is applied.

[0041] As the crosslinking agent, compounds such as melamine, isocyanate, carbodiimide, and oxazoline, which are crosslinkable with hydroxyl groups and have a nitrogen element, are suitable as the crosslinking agent. Among them, melamine compounds or isocyanate compounds are preferred from the viewpoint of stability over time of the coating solution and reactivity with the hydroxyl groups of polyvinyl alcohol resins. This is because carbodiimide crosslinking agents react with carboxyl groups, whereas melamine compounds or isocyanate compounds react with hydroxyl groups, and therefore form a crosslinked structure more suitably with polyvinyl alcohol resins having hydroxyl groups as functional groups. Among them, isocyanate compounds are particularly preferred from the viewpoint of forming a crosslinking reaction suitably with the hydroxyl groups of polyvinyl alcohol resins and having excellent transparency. In the present invention, in order to improve the strength of the coating film, two or more crosslinking agents having a nitrogen element may be mixed. In addition, a catalyst other than organotin may be used to promote the crosslinking reaction.

[0042] As the isocyanate compound, low molecular weight or high molecular weight diisocyanates or trivalent or higher polyisocyanates can be used. For example, as the isocyanate compound, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate, 1,5-naphthylene diisocyanate, 1,4-naphthylene diisocyanate, phenylene diisocyanate, tetramethylxylylene diisocyanate, 4,4'-diphenylether diisocyanate, 2-nitrodiphenyl-4,4'-diisocyanate, 2,2'-diphenylpropane-4,4'-diisocyanate, 3,3'-dimethyldiphenylmethane aromatic diisocyanates such as 4,4'-diisocyanate, 4,4'-diphenylpropane diisocyanate, and 3,3'-dimethoxydiphenyl-4,4'-diisocyanate; aromatic aliphatic diisocyanates such as xylylene diisocyanate; alicyclic diisocyanates such as isophorone diisocyanate, 4,4-dicyclohexylmethane diisocyanate, and 1,3-bis(isocyanatemethyl)cyclohexane; aliphatic diisocyanates such as hexamethylene diisocyanate and 2,2,4-trimethylhexamethylene diisocyanate; and trimers of these isocyanate compounds. Further, the polymer terminal isocyanate group-containing compound obtained by reacting an excess amount of these isocyanate compounds with low molecular weight active hydrogen compounds such as ethylene glycol, propylene glycol, trimethylolpropane, glycerin, sorbitol, ethylenediamine, monoethanolamine, diethanolamine, triethanolamine, or high molecular weight active hydrogen compounds such as polyester polyols, polyether polyols, and polyamides can be mentioned. From the viewpoints of transparency, adhesion, and wet heat resistance, aliphatic and alicyclic isocyanates and their modified products are preferred. When aromatic isocyanates are used, there is a problem of yellowing, and they may not be preferred for optical applications that require high transparency.Furthermore, compared with aliphatic systems, the coating film is stronger and harder, so it becomes unable to relieve stress caused by the shrinkage and swelling of various resins, etc., and this can result in reduced adhesion.

[0043] As the crosslinking agent used in the present invention, a blocked isocyanate compound is also preferable. By adding a blocked isocyanate compound, it becomes possible to more suitably improve the stability over time of the coating liquid.

[0044] The blocked isocyanate compound can be prepared by addition reaction of the above-mentioned isocyanate compound with a blocking agent by a conventionally known method. Examples of the isocyanate blocking agent include phenols such as phenol, cresol, xylenol, resorcinol, nitrophenol, and chlorophenol; thiophenols such as thiophenol and methylthiophenol; oximes such as acetoxime, methylethylketoxime, and cyclohexanoneoxime; pyrazole compounds such as 3,5-dimethylpyrazole, 3-methylpyrazole, 4-bromo-3,5-dimethylpyrazole, and 4-nitro-3,5-dimethylpyrazole; alcohols such as methanol, ethanol, propanol, and butanol; ethylene chlorohydrin, 1,3-dichloro-2-propanol, and the like; Examples of such compounds include halogen-substituted alcohols such as propyl alcohol; tertiary alcohols such as t-butanol and t-pentanol; lactams such as ε-caprolactam, δ-valerolactam, γ-butyrolactam, and β-propyllactam; aromatic amines; imides; active methylene compounds such as acetylacetone, acetoacetate, ethyl malonate, and diesters of malonic acid (dimethyl malonate, diethyl malonate, di-n-butyl malonate, and di-2-ethylhexyl malonate); triazole compounds such as 1,2,4-triazole; mercaptans; imines; ureas; diaryl compounds; and sodium bisulfite.

[0045] The dissociation temperature of the blocked isocyanate is preferably 130°C or less, more preferably 125°C or less, and even more preferably 120°C or less. The blocking agent dissociates from the functional group by heat addition in the drying process after coating of the coating liquid or in the case of the in-line coating method in the film forming process, and a regenerated isocyanate group is generated. Therefore, a crosslinking reaction with polyvinyl alcohol resin etc. progresses, and the adhesiveness at room temperature and high temperature and high humidity is improved. When the dissociation temperature of the blocked isocyanate is below the above temperature, the dissociation of the blocking agent progresses sufficiently, so that the adhesiveness, especially the wet heat resistance, is good. The lower limit of the dissociation temperature is not particularly limited as long as it is above room temperature in order to stabilize the coating liquid, but is preferably 50°C or more, more preferably 80°C or more. The dissociation temperature and boiling point can be measured by differential thermal analysis.

[0046] Examples of blocking agents having a dissociation temperature of 130° C. or less used in blocked isocyanates include pyrazole compounds: 3,5-dimethylpyrazole, 3-methylpyrazole, 4-bromo-3,5-dimethylpyrazole, 4-nitro-3,5-dimethylpyrazole, etc., active methylene compounds: malonic acid diesters (dimethyl malonate, diethyl malonate, di-n-butyl malonate, di-2-ethylhexyl malonate), etc., and triazole compounds: 1,2,4-triazole, etc. Among these, pyrazole compounds are preferred from the viewpoint of wet heat resistance and yellowing, and active methylene compounds are preferred from the viewpoint of reactivity. Bisulfite compounds such as sodium bisulfite are also included in this range, but it is preferable to use them with caution because if the salt remains in the coating layer, water resistance may decrease.

[0047] Polyisocyanates, which are precursors of blocked isocyanates, can be obtained by introducing diisocyanates, such as urethane-modified diisocyanates, allophanate-modified diisocyanates, urea-modified diisocyanates, biuret-modified diisocyanates, uretdione-modified diisocyanates, uretoimine-modified diisocyanates, isocyanurate-modified diisocyanates, and carbodiimide-modified diisocyanates.

[0048] Blocked isocyanates can introduce hydrophilic groups into the precursor polyisocyanate to impart water solubility or water dispersibility. Examples of hydrophilic groups include (1) quaternary ammonium salts of dialkylamino alcohols and quaternary ammonium salts of dialkylaminoalkylamines, (2) sulfonates, carboxylates, phosphates, and (3) polyethylene glycols and polypropylene glycols with one end blocked with an alkoxy group. When a hydrophilic moiety is introduced, the isocyanate becomes (1) cationic, (2) anionic, or (3) nonionic. Among them, since most other water-soluble resins are anionic, anionic and nonionic are preferred because they are easily compatible. In addition, anionic isocyanates have excellent compatibility with other resins, and nonionic isocyanates do not have ionic hydrophilic groups, so they are also preferred for improving resistance to moist heat. In addition, anionic and cationic isocyanates may aggregate with other resins or self-aggregate, which may affect transparency and appearance, so nonionic is more preferred among the above.

[0049] The anionic hydrophilic group is preferably one having a hydroxyl group for introduction into polyisocyanate and a carboxylic acid group for imparting hydrophilicity. Examples include glycolic acid, lactic acid, tartaric acid, citric acid, oxybutyric acid, oxyvaleric acid, hydroxypivalic acid, dimethylolacetic acid, dimethylolpropionic acid, dimethylolbutanoic acid, and polycaprolactone having a carboxylic acid group. To neutralize the carboxylic acid group, an organic amine compound is preferred. For example, linear or branched primary, secondary or tertiary amines having 1 to 20 carbon atoms, such as ammonia, methylamine, ethylamine, propylamine, isopropylamine, butylamine, 2-ethylhexylamine, cyclohexylamine, dimethylamine, diethylamine, dipropylamine, diisopropylamine, dibutylamine, trimethylamine, triethylamine, triisopropylamine, tributylamine, or ethylenediamine; cyclic amines, such as morpholine, N-alkylmorpholine, or pyridine; and hydroxyl group-containing amines, such as monoisopropanolamine, methylethanolamine, methylisopropanolamine, dimethylethanolamine, diisopropanolamine, diethanolamine, triethanolamine, diethylethanolamine, or triethanolamine.

[0050] As the nonionic hydrophilic group, the number of repeating units of ethylene oxide and / or propylene oxide of polyethylene glycol or polypropylene glycol capped at one end with an alkoxy group is preferably 3 to 50, more preferably 5 to 30. If the number of repeating units is small, the compatibility with the resin becomes poor and the haze increases, whereas if the number of repeating units is large, the adhesiveness under high temperature and high humidity conditions may decrease.

[0051] To improve the water dispersibility of the blocked isocyanate, a nonionic, anionic, cationic or amphoteric surfactant can be added. Examples of such surfactants include nonionic surfactants such as polyethylene glycol and polyhydric alcohol fatty acid esters, anionic surfactants such as fatty acid salts, alkyl sulfate esters, alkylbenzene sulfonates, sulfosuccinates and alkyl phosphates, cationic surfactants such as alkylamine salts and alkylbetaines, amine carboxylates, amine sulfonates and sulfate salts.

[0052] In addition to water, a water-soluble organic solvent may be contained. For example, the organic solvent used in the reaction may be removed and another organic solvent may be added.

[0053] The content of the blocked isocyanate is preferably 5% by mass or more and 100% by mass or less relative to the polyvinyl alcohol-based resin, and more preferably 15% by mass or more and 70% by mass or less. If the content is too small, crosslinking of the coating layer is insufficient, and adhesion to the water-soluble resin, hydrophilic resin, or polarizer decreases, whereas if the content is too large, the amount of hydroxyl groups in the polyvinyl alcohol-based resin decreases, and adhesion to the water-soluble resin, hydrophilic resin, or polarizer at room temperature decreases.

[0054] The active methylene blocked isocyanate crosslinking agent preferably used in the present invention can be synthesized by reacting the isocyanate group of an isocyanate compound with an active methylene compound.

[0055] Examples of active methylene compounds include Meldrum's acid, dialkyl malonates (e.g., dimethyl malonate, diethyl malonate, di-n-butyl malonate, di-t-butyl malonate, di-2-ethylhexyl malonate, methyl n-butyl malonate, ethyl n-butyl malonate, methyl s-butyl malonate, ethyl s-butyl malonate, methyl t-butyl malonate, ethyl t-butyl malonate, diethyl methylmalonate, dibenzyl malonate, diphenyl malonate, benzyl methyl malonate, ethyl phenyl malonate, t-butylphenyl malonate, isopropylidene malonate, etc.), alkyl acetoacetates (e.g., methyl acetoacetate, ethyl acetoacetate, n-propyl acetoacetate, isopropyl acetoacetate, n-butyl acetoacetate, t-butyl acetoacetate, benzyl acetoacetate, phenyl acetoacetate, etc.), 2-acetoacetoxyethyl methacrylate, acetylacetone, ethyl cyanoacetate, etc. Dimethyl malonate and diethyl malonate are preferred in that they have excellent low-temperature curing properties.

[0056] The melamine-based compound preferably used in the present invention is a compound having a melamine skeleton in the compound, and for example, an alkylolated melamine derivative, a compound partially or completely etherified by reacting an alcohol with an alkylolated melamine derivative, and a mixture thereof can be used. As the alcohol used for etherification, methyl alcohol, ethyl alcohol, isopropyl alcohol, n-butanol, isobutanol, etc. are preferably used. In addition, the melamine compound may be either a monomer or a dimer or higher polymer, or a mixture thereof may be used. Furthermore, a product obtained by co-condensing a part of melamine with urea or the like can also be used, and a catalyst other than an organotin catalyst can also be used to increase the reactivity of the melamine compound.

[0057] The carbodiimide compound preferably used in the present invention is a compound having a carbodiimide group, which is a compound having at least one carbodiimide group represented by (-N=C=N-) in the molecule, and can be produced by heating an organic isocyanate and subjecting it to a decarboxylation reaction.

[0058] Examples of carbodiimide compounds preferably used in the present invention include diphenylcarbodiimide, di-cyclohexylcarbodiimide, di-2,6-dimethylphenylcarbodiimide, diisopropylcarbodiimide, dioctyldecylcarbodiimide, di-o-toluylcarbodiimide, di-p-toluylcarbodiimide, di-p-nitrophenylcarbodiimide, di-p-aminophenylcarbodiimide, di-p-hydroxyphenylcarbodiimide, di-p-chlorophenylcarbodiimide, di- o-Chlorophenylcarbodiimide, di-3,4-dichlorophenylcarbodiimide, di-2,5-dichlorophenylcarbodiimide, p-phenylene-bis-o-tolylcarbodiimide, p-phenylene-bis-dicyclohexylcarbodiimide, p-phenylene-bis-di-p-chlorophenylcarbodiimide, 2,6,2,6-tetraisopropyldiphenylcarbodiimide, hexamethylene-bis-cyclohexylcarbodiimide, ethylene-bis-diphenylcarbodiimide, ethylene-bis- Di-cyclohexylcarbodiimide, N,N-di-o-triylcarbodiimide, N,N-diphenylcarbodiimide, N,N-dioctyldecylcarbodiimide, N,N-di-2,6-dimethylphenylcarbodiimide, N-triyl-N-cyclohexylcarbodiimide, N,N-di-2,6-diisopropylphenylcarbodiimide, N,N-di-2,6-di-tert-butylphenylcarbodiimide, N-toluyl-N-phenylcarbodiimide, N,N-di-p-nitrophenylcarbodiimide, N,N-di-p-aminophenylcarbodiimide, N,N- Di-p-hydroxyphenylcarbodiimide, N,N-di-cyclohexylcarbodiimide, N,N-di-p-toluylcarbodiimide, N,N-benzylcarbodiimide, N-octadecyl-N-phenylcarbodiimide, N-benzyl-N-phenylcarbodiimide, N-octadecyl-N-triylcarbodiimide, N-cyclohexyl-N-triylcarbodiimide, N-phenyl-N-triylcarbodiimide, N-benzyl-N-triylcarbodiimide, N,N-di-o-ethylphenylcarbodiimide, N,N-di-p-ethylphenylcarbodiimide, N,N-di-o-isopropylphenylcarbodiimide, N,Mono- or dicarbodiimide compounds such as N-di-p-isopropylphenylcarbodiimide, N,N-di-o-isobutylphenylcarbodiimide, N,N-di-p-isobutylphenylcarbodiimide, N,N-di-2,6-diethylphenylcarbodiimide, N,N-di-2-ethyl-6-isopropylphenylcarbodiimide, N,N-di-2-isobutyl-6-isopropylphenylcarbodiimide, N,N-di-2,4,6-trimethylphenylcarbodiimide, N,N-di-2,4,6-triisopropylphenylcarbodiimide, and N,N-di-2,4,6-triisobutylphenylcarbodiimide; poly(1,6-hexamethylenecarbodiimide), poly(4,4-methylenebiscyclohexylcarbodiimide), and poly(1,3-cyclohexylenecarbodiimide) Examples of the polycarbodiimides include poly(1,4-cyclohexylenecarbodiimide), poly(4,4-diphenylmethanecarbodiimide), poly(3,3-dimethyl-4,4-diphenylmethanecarbodiimide), poly(naphthylenecarbodiimide), poly(p-phenylenecarbodiimide), poly(m-phenylenecarbodiimide), poly(triylcarbodiimide), poly(diisopropylcarbodiimide), poly(methyl-diisopropylphenylenecarbodiimide), poly(triethylphenylenecarbodiimide), poly(triisopropylphenylenecarbodiimide), poly(1,3,5-triisopropylphenylene-2,4-carbodiimide), and poly(1,5-diisopropylphenylene-2,4-carbodiimide).

[0059] Carbodiimide compounds can be synthesized by conventionally known techniques, and generally, condensation reaction of diisocyanate compounds is used.Diisocyanate compounds are not particularly limited, and both aromatic and aliphatic compounds can be used, and specific examples include tolylene diisocyanate, xylene diisocyanate, diphenylmethane diisocyanate, phenylene diisocyanate, naphthalene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, cyclohexane diisocyanate, methylcyclohexane diisocyanate, isophorone diisocyanate, dicyclohexyl diisocyanate, dicyclohexylmethane diisocyanate, etc.

[0060] The content of carbodiimide groups contained in the carbodiimide compound, in terms of carbodiimide equivalent (weight [g] of the carbodiimide compound required to give 1 mol of carbodiimide groups), is usually in the range of 100 to 1000, preferably 250 to 800, and more preferably 300 to 700. Use within the above range improves the durability of the coating film.

[0061] Furthermore, in order to improve the water solubility or water dispersibility of the polycarbodiimide-based compound, a surfactant may be added, or a hydrophilic monomer such as a polyalkylene oxide, a quaternary ammonium salt of a dialkylamino alcohol, or a hydroxyalkylsulfonate may be added, within a range that does not impair the effects of the present invention.

[0062] In the present invention, examples of compounds containing an oxazoline group include 2-methoxy-2-oxazoline, 2-ethoxy-2-oxazoline, 2-propoxy-2-oxazoline, 2-butoxy-2-oxazoline, 2-pentyloxy-2-oxazoline, 2-hexyloxy-2-oxazoline, 2-heptyloxy-2-oxazoline, 2-octyloxy-2-oxazoline, 2-nonyloxy-2-oxazoline, 2-decyloxy-2-oxazoline, 2-cyclopentyloxy-2-oxazoline, 2-cyclohexyloxy-2-oxazoline, 2-allyloxy-2-oxazoline, 2-methallyloxy-2-oxazoline, 2-crotyloxy-2-oxazoline, 2-phenoxy-2-oxazoline, Oxazoline, 2-cresyl-2-oxazoline, 2-o-ethylphenoxy-2-oxazoline, 2-o-propylphenoxy-2-oxazoline, 2-o-phenylphenoxy-2-oxazoline, 2-m-ethylphenoxy-2-oxazoline, 2-m-propylphenoxy-2-oxazoline, 2-p- Phenylphenoxy-2-oxazoline, 2-methyl-2-oxazoline, 2-ethyl-2-oxazoline, 2-propyl-2-oxazoline, 2-butyl-2-oxazoline, 2-pentyl-2-oxazoline, 2-hexyl-2-oxazoline, 2-heptyl-2-oxazoline, 2-octyl-2-oxazoline, 2-nonyl-2-oxazoline, 2-decyl-2-oxazoline, 2-cyclopentyl-2-oxazoline, 2-cyclohexyl-2-oxazoline, 2-allyl-2-oxazoline, 2-methallyl-2-oxazoline, 2-crotyl-2-oxazoline, 2-phenyl-2-oxazoline, 2-o-ethylphenyl-2-oxazoline, 2-o-propylphenyl-2-oxazoline, 2-o-phenylphenyl-2-oxazoline, 2-m-ethylphenyl-2- Oxazoline, 2-m-propylphenyl-2-oxazoline, 2-p-phenylphenyl-2-oxazoline, 2,2-bis(2-oxazoline), 2,2-bis(4-methyl-2-oxazoline), 2,2-bis(4,4-dimethyl-2-oxazoline), 2,2-bis(4-ethyl-2-oxazoline), 2,2-bis(4,4-diethyl-2-oxazoline), 2,2-bis(4-propyl-2-oxazoline), 2,2-bis(4-butyl-2-oxazoline), 2,2-bis(4-hexyl-2-oxazoline), 2,2-bis(4-phenyl-2-oxazoline), 2,2-bis(4-cyclohexyl-2-oxazoline), 2,2-bis(4-benzyl-2-oxazoline), 2,2-p-phenylenebis(2-oxazoline), 2,2-m-phenylenebis(2-oxazoline), 2,2-o-phenylenebis(2-oxazoline), 2,2-p-phenylenebis( 4-Methyl-2-oxazoline), 2,2-p-phenylenebis(4,4-dimethyl-2-oxazoline), 2,2-m-phenylenebis(4-methyl-2-oxazoline), 2,2-m-phenylenebis(4,4-dimethyl-2-oxazoline), 2,2-ethylenebis(2-oxazoline), 2,2-tetramethylenebis(2-oxazoline), 2,2-hexamethylenebis(2-oxazoline), 2,2-octyl Examples of the oxazoline include tamethylene bis(2-oxazoline), 2,2-decamethylene bis(2-oxazoline), 2,2-ethylene bis(4-methyl-2-oxazoline), 2,2-tetramethylene bis(4,4-dimethyl-2-oxazoline), 2,2-9,9-diphenoxyethane bis(2-oxazoline), 2,2-cyclohexylene bis(2-oxazoline), and 2,2-diphenylene bis(2-oxazoline). Further examples include polyoxazoline compounds containing the above-mentioned compounds as monomer units.

[0063] When the total solid content of the polyester resin, polyvinyl alcohol resin, and nitrogen-containing crosslinking agent in the coating liquid is 100% by mass, the lower limit of the content of the nitrogen-containing crosslinking agent is preferably 0.1% by mass (in the solid content), more preferably 1% by mass, even more preferably 2% by mass, particularly preferably 3% by mass, and most preferably 4% by mass. When the content of the nitrogen-containing crosslinking agent is 0.1% by mass or more, the adhesion to the polyvinyl alcohol resin of the polarizer or hydrophilic adhesive, and the urethane resin of the photocurable adhesive is good, and even if water adheres to the polyester film or the easy-adhesion layer, blocking is unlikely to occur and there is no risk of the peel strength increasing. The upper limit of the content of the nitrogen-containing crosslinking agent is preferably 60% by mass, more preferably 40% by mass, even more preferably 20% by mass, particularly preferably 15% by mass, and most preferably 9.4% by mass. When the content of the nitrogen-containing crosslinking agent is 60% by mass or less, the adhesion to the functional layer such as the adhesive layer is good, which is preferable.

[0064] The blending ratio of the polyester resin to the polyvinyl alcohol resin is preferably 1 to 30 by mass, and more preferably 2 to 20. When the blending ratio is 1 or more, the adhesiveness to the polyester film is favorable, and when the blending ratio is 30 or less, the adhesiveness to the polyvinyl alcohol resin layer of the polarizer, adhesive, or the like is favorable.

[0065] The sum of the polyester resin and the polyvinyl alcohol resin to the nitrogen-containing crosslinking agent is preferably in a mass ratio of 3 to 20, more preferably 7 to 15. When the blending ratio is 3 or more, it is suitable for the development of an adhesive effect by the binder resin component, and when it is 20 or less, it is suitable for the adhesive effect by phase separation.

[0066] The adhesive layer in the present invention, by adopting the above composition, exhibits high adhesiveness (adhesion) to a polarizer, a hydrophilic adhesive, and a photocurable adhesive. Specifically, the remaining area after one peeling from a hydrophilic adhesive or a photocurable adhesive in an adhesiveness test described later is preferably 90% or more, more preferably 95% or more, and even more preferably 100%.

[0067] (Organotin catalyst) Organotin, especially tributyltin, is listed in the "List of Chemical Substances Suspected of Having Endocrine Disrupting Effects" published by the Ministry of the Environment in 2000 and is designated as a substance for which the risk is evaluated as a priority. Therefore, it is necessary to avoid using it, but in the future, it is necessary to avoid using even organotin that is not listed as such as much as possible and reduce the risk to the human body and the environment as much as possible. For the above reasons, it is preferable not to intentionally use organotin as a crosslinking / curing catalyst in the easy-adhesion layer. However, this does not deny the inclusion of 100 ppm or less in the easy-adhesion layer without intentional use. In other words, in the present invention, "substantially free of organotin as a curing catalyst for the composition in the easy-adhesion layer" means that the amount of organotin is 100 ppm or less relative to the total mass of the solid content of the easy-adhesion layer. In the present invention, since the coating solution for forming the easy-adhesion layer contains the above-mentioned crosslinking agent having a nitrogen element, the easy-adhesion layer is quickly crosslinked and cured when heated even without a catalyst, and the produced easy-adhesion polyester film does not have the risk of blocking even in the presence of liquid water, but if necessary, a catalyst other than tin that is not environmentally problematic may be used. For example, such catalysts include zinc-based compounds such as zinc acetylacetonate, zinc propionate, and zinc octanoate, titanium-based compounds such as tetraisopropyl titanate and tetra-n-butyl titanate, zirconium-based compounds such as zirconium tetraisopropoxide and zirconium tetra-n-butoxide, bismuth-based compounds such as bis(acetylacetonate)bismuth and bismuth 2-ethylhexanoate, acid curing catalysts such as p-toluenesulfonic acid, and amines. The content of the organotin catalyst in the easy-adhesion layer was measured as follows. The adhesive layer on the corresponding surface of the film is wiped off using a solvent that can be wiped off, such as MEK, and the wiping is considered complete when the surface of the adhesive layer on the corresponding surface is subjected to fluorescent X-ray measurement and the Si peak intensity becomes 1 / 100 or less of the value before wiping. The mass of the A4 film is then measured before and after wiping, and the difference is regarded as the post-dry coating amount of the adhesive layer on the corresponding surface. The adhesive layer of the corresponding film is dissolved, and Tsuyoshi The content of the organotin catalyst in the adhesive layer was finally calculated using a method similar to that described in Kawakami et al., YAKUGAKU ZASSHI 130(2)223-235(2010).

[0068] When the adhesive layer contained an organotin catalyst, the adhesion between the photocurable adhesive and the adhesive layer tended to decrease. This is presumably because the organotin catalyst reduced the activity of the photocation catalyst.

[0069] (Additives) The adhesive layer of the present invention may contain known additives, such as surfactants, antioxidants, heat stabilizers, weather stabilizers, ultraviolet absorbers, organic lubricants, pigments, dyes, organic or inorganic particles, antistatic agents, nucleating agents, etc., within the range that does not impair the effects of the present invention. However, those with high environmental toxicity are excluded.

[0070] In the present invention, in order to further improve the blocking resistance of the easy-adhesion layer, it is also a preferred embodiment to add particles to the easy-adhesion layer.The particles contained in the easy-adhesion layer in the present invention are, for example, titanium oxide, barium sulfate, calcium carbonate, calcium sulfate, silica, alumina, talc, kaolin, clay, etc., or mixtures thereof, and further include inorganic particles such as calcium phosphate, mica, hectorite, zirconia, tungsten oxide, lithium fluoride, calcium fluoride, etc., used in combination, and organic polymer particles such as styrene, acrylic, melamine, benzoguanamine, silicone, etc.

[0071] The average particle size of the inactive particles in the easy-adhesion layer (average particle size based on the number of particles measured by SEM; the same applies below) is preferably 0.04 to 2.0 μm, and more preferably 0.1 to 1.0 μm. When the average particle size of the inactive particles is 0.04 μm or more, it is easy to form unevenness on the film surface, which improves the handling properties such as the slipperiness and winding properties of the film, and the processability during lamination is good, which is preferable. On the other hand, when the average particle size of the inactive particles is 2.0 μm or less, the particles are less likely to fall off, which is preferable. The particle concentration in the easy-adhesion layer is preferably 1 to 20 mass % of the solid component.

[0072] In the present invention, the thickness of the easy-adhesion layer can be appropriately set in the range of 0.001 to 2.00 μm, but in order to achieve both processability and adhesiveness, the thickness is preferably in the range of 0.01 to 1.00 μm, more preferably 0.02 to 0.80 μm, and even more preferably 0.05 to 0.50 μm. If the thickness of the easy-adhesion layer is 0.001 μm or more, the adhesiveness is good, which is preferable. If the thickness of the easy-adhesion layer is 2.00 μm or less, blocking is unlikely to occur, which is preferable.

[0073] Conventionally, many of the polyester films having an easy-adhesion layer containing a polyester resin, a polyvinyl alcohol resin, and a crosslinking agent have satisfied blocking resistance when left in an environment containing normal water vapor. However, in winter, when transported between outdoors and indoors, condensation may occur and liquid water may adhere to the film surface or the easy-adhesion layer surface, and at that time, the polyester film having an easy-adhesion layer containing a polyester resin, a polyvinyl alcohol resin, and a crosslinking agent has a problem of blocking. However, the easy-adhesion polyester film of the present invention not only has blocking resistance when left in an environment containing normal water vapor, but also has no risk of blocking even when the easy-adhesion polyester film transported between indoors and outdoors in winter condenses with a change in environmental temperature and liquid water adheres to the film surface or the easy-adhesion layer surface. This can be confirmed by the fact that the peel force after water adhesion is 2 N / cm or less according to the measurement method described below. More preferably, it is 1.5 N / cm or less, even more preferably 1 N / cm or less, particularly preferably 0.5 N / cm or less, and most preferably 0.3 N / cm or less. The peel strength after adhesion of water is preferably small, but is also preferably 0.01 N / cm or more, and is also preferably 0.02 N / cm or more.

[0074] In addition, when the surface of the adhesive layer of the adhesive polyester film is measured by ESCA (X-ray photoelectron spectrometry), it is preferable that the nitrogen element content of the surface constituent elements is 2.0 at% or more because it improves adhesion with hydrophilic adhesives and photocurable adhesives, and it is also preferable that blocking is unlikely to occur and the peel strength is kept small even when liquid water is attached. In addition, it is preferable that the nitrogen element content is 3.0 at% or less because it improves adhesion with hydrophilic adhesives and photocurable adhesives. For this reason, the nitrogen element content of the surface constituent elements is more preferably 2.2 at% or more and 2.8 at% or less, and even more preferably 2.4 at% or more and 2.6 at% or less.

[0075] The method of localizing the nitrogen element on the surface is not particularly limited, but for example, the temperature and holding time during drying of the applied easy-adhesion layer can be controlled. By optimally setting these, the content of the nitrogen element in the surface constituent elements can be effectively controlled within the expected range. In order to localize the nitrogen element on the surface, the drying temperature is preferably 75°C or higher and 100°C or lower, and the drying time is preferably 5 seconds or higher and 15 seconds or lower. More preferably, the drying temperature is 80°C or higher and 95°C or lower, and the drying time is 7 seconds or higher and 13 seconds or lower. When the drying temperature is 75°C or higher, the amount of heat is sufficient, and the nitrogen element present in the easy-adhesion layer is easily moved to the easy-adhesion layer surface, which is preferable. When the drying time is 5 seconds or longer, the amount of heat is sufficient, and the nitrogen element present in the easy-adhesion layer is easily moved to the easy-adhesion layer surface, which is preferable. When the drying temperature is 100°C or lower, the amount of heat is not excessive, and the movement of the nitrogen element to the easy-adhesion layer surface does not increase too much, which is preferable. In addition, the drying time is preferably 15 seconds or less, since this prevents excessive heat and prevents excessive migration of nitrogen elements to the surface of the easy-adhesion layer.

[0076] In the present invention, the easy-adhesion layer formed by curing a composition containing a polyester resin, a polyvinyl alcohol resin, and a crosslinking agent having a nitrogen element may be laminated on at least one side of the polyester film, and of course, the easy-adhesion layer may be laminated on both sides. Also, the easy-adhesion layer may be laminated on only one side of the polyester film, and a resin coating layer of a different composition may be laminated on the other film surface. The easy-adhesion layer formed by curing a composition containing a polyester resin, a polyvinyl alcohol resin, and a crosslinking agent having a nitrogen element in the present invention has excellent adhesion and adhesion to a polarizer made of a polyvinyl alcohol film and a dichroic material such as iodine, a hydrophilic adhesive such as a polyvinyl alcohol resin, and a photocurable adhesive mainly composed of a urethane resin, but also has a certain degree of adhesion and adhesion to other functional layers such as a hard coat layer.

[0077] In the present invention, the expression that the easy-adhesion layer is formed by curing a composition containing a polyester resin, a polyvinyl alcohol resin, and a crosslinking agent having a nitrogen element is used because, although it is considered that the hydroxyl group of the polyvinyl alcohol reacts with the functional group of the crosslinking agent to crosslink and harden the easy-adhesion layer after crosslinking and hardening, it is extremely difficult or impossible to accurately express the composition and chemical structure after crosslinking and hardening. Therefore, most of the polyester resin, polyvinyl alcohol resin, and crosslinking agent having a nitrogen element in the crosslinked and hardened easy-adhesion layer do not exist in their original chemical structures.

[0078] (Production of Highly Adhesive Polyester Film for Protecting Polarizers) The method for producing the highly adhesive polyester film for protecting a polarizer of the present invention will be described using a polyethylene terephthalate (hereinafter abbreviated as PET) film as an example, but the method is of course not limited thereto.

[0079] After thoroughly drying the PET resin in a vacuum, it is fed to an extruder, and the molten PET resin at about 280°C is extruded from a T-die into a sheet shape onto a rotating cooling roll, and cooled and solidified by an electrostatic application method to obtain an unstretched PET sheet. The unstretched PET sheet may be a single layer structure or a multilayer structure formed by a coextrusion method.

[0080] The obtained unstretched PET sheet is uniaxially or biaxially stretched to obtain a uniaxially stretched PET film. For example, in the case of biaxial stretching, the film is stretched 2.5 to 5.0 times in the longitudinal direction with a roll heated to 80 to 120°C to obtain a uniaxially stretched PET film, and the ends of the film are held with clips and introduced into a hot air zone heated to 80 to 180°C, where it is stretched 2.5 to 5.0 times in the width direction. In the case of uniaxial stretching, the film is stretched 2.5 to 5.0 times in a tenter. After stretching, the film is introduced into a heat treatment zone and heat-treated to complete the crystal orientation.

[0081] The lower limit of the temperature of the heat treatment zone is preferably 170°C, more preferably 180°C. When the temperature of the heat treatment zone is 170°C or higher, curing is sufficient, blocking properties in the presence of liquid water are good, and it is preferable, and there is no need to extend the drying time. On the other hand, the upper limit of the temperature of the heat treatment zone is preferably 230°C, more preferably 200°C. When the temperature of the heat treatment zone is 230°C or lower, it is preferable because there is no risk of the physical properties of the film decreasing. In the manufacturing process for the use of a polarizer protective film, it is more preferable to perform heat treatment at 200°C or lower in order to suppress the decrease in the refractive index.

[0082] The easy-adhesion layer can be provided after the film is produced or during the production process. In particular, from the viewpoint of productivity, it is preferable to form the easy-adhesion layer by applying a coating liquid to at least one side of the PET film, which is not yet stretched or has been uniaxially stretched, at any stage of the film production process. In this case, the drying conditions for the coating liquid are preferably a temperature of 75° C. or higher and 100° C. or lower, and a drying time of 5 seconds or higher and 15 seconds or lower.

[0083] The coating solution can be applied to the PET film by any known method. For example, reverse roll coating, gravure coating, kiss coating, die coater, roll brush, spray coating, air knife coating, wire bar coating, pipe doctor, impregnation coating, curtain coating, etc. These methods can be used alone or in combination.

[0084] (Polarizing plate) The easily adhesive polyester film of the present invention can be suitably used as a polarizer protective film. In general, a polarizing plate is formed by disposing a polarizer protective film on both sides of a polarizer, and it is preferable that the polarizer protective film on at least one side of the polarizer is the easily adhesive polyester film for polarizer protection. The other polarizer protective film may be the easily adhesive polyester film of the present invention, or it is also preferable to use a film without birefringence, such as a triacetyl cellulose film, an acrylic film, or a norbornene-based film.

[0085] Examples of polarizers include polyvinyl alcohol-based films containing a dichroic material such as iodine. The polarizer protective film is bonded to the polarizer directly or via an adhesive layer, and from the viewpoint of improving adhesion, it is preferable to bond them via an adhesive. In this case, it is preferable to arrange the easy-adhesion layer of the present invention on the polarizer surface or the adhesive layer surface. Examples of polarizers that are preferable for bonding the polyester film of the present invention include polarizers obtained by dyeing and adsorbing iodine or a dichroic material to a polyvinyl alcohol-based film, uniaxially stretching the film in an aqueous boric acid solution, and washing and drying the film while maintaining the stretched state. The stretching ratio of the uniaxial stretching is usually about 4 to 8 times. Polyvinyl alcohol is suitable as the polyvinyl alcohol-based film, and commercially available products such as "Kuraray Vinylon" [manufactured by Kuraray Co., Ltd.], "Tohcello Vinylon" [manufactured by Tohcello Co., Ltd.], and "Nippon Vinylon" [manufactured by Nippon Synthetic Chemical Industry Co., Ltd.] can be used. Examples of dichroic materials include iodine, disazo compounds, and polymethine dyes.

[0086] When the adhesive layer to be applied to the polarizer is to be thin, it is preferable that the adhesive is water-based, that is, that the adhesive component is dissolved or dispersed in water. For example, a composition using a polyvinyl alcohol resin, a urethane resin, or the like as the main component and, if necessary, blending an isocyanate compound, an epoxy compound, or the like, can be used to improve adhesion. The thickness of the adhesive layer is preferably 5 μm or less, more preferably 3 μm or less, and even more preferably 1 μm or less.

[0087] When a polyvinyl alcohol resin is used as the main component of the adhesive, modified polyvinyl alcohol resins such as partially saponified polyvinyl alcohol, fully saponified polyvinyl alcohol, carboxyl group-modified polyvinyl alcohol, acetoacetyl group-modified polyvinyl alcohol, methylol group-modified polyvinyl alcohol, and amino group-modified polyvinyl alcohol may be used. The concentration of the polyvinyl alcohol resin in the adhesive is preferably 1 to 10% by mass, and more preferably 2 to 7% by mass.

[0088] When it is desired to further increase productivity, it is preferable to use a photocurable adhesive as the adhesive to be applied to the polarizer. The thickness of the adhesive layer after curing can be set arbitrarily depending on the design of the polarizing plate characteristics, but it is preferable to have a smaller thickness from the viewpoint of reducing the adhesive material cost. In general, it is 0.01 to 20 μm, preferably 0.1 to 10 μm, and more preferably 0.5 to 5 μm. When the adhesive layer is 0.01 μm or more thick, air bubbles are unlikely to be mixed into the adhesive layer, and the adhesiveness and durability are good, which is preferable. When the adhesive layer is 20 μm or less, the reaction rate of the adhesive is sufficient, and the wet heat resistance of the polarizing plate is good, which is preferable.

[0089] The photocurable adhesive preferably contains an epoxy compound containing no aromatic ring as a main component, a photocationically curable component (I), and a photocationic polymerization initiator (II).

[0090] The photocurable adhesive preferably contains an epoxy compound that does not contain an aromatic ring as a main component. The epoxy compound that does not contain an aromatic ring is an epoxy compound other than an aromatic epoxy compound, and is hereinafter referred to as an aliphatic epoxy compound. An "epoxy compound" is a compound having at least one epoxy group in the molecule. The aliphatic epoxy compound that is the main component may contain two or more epoxy compounds. The "main component" means that the content of the aliphatic epoxy compound is 50% by mass or more in 100% by mass of the photocurable adhesive. The content of the aliphatic epoxy compound is preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and even more preferably 90% by mass or more.

[0091] The aliphatic epoxy compound may be an epoxy compound having an alicyclic ring, or may be an epoxy compound not containing an alicyclic ring and consisting only of a linear hydrocarbon structure and / or a branched hydrocarbon structure. The aliphatic epoxy compound may contain an unsaturated bond such as a double bond, and may further contain a heteroatom (oxygen atom, nitrogen atom, sulfur atom, halogen atom, etc.) other than the oxygen atom contained in the epoxy group.

[0092] Photocationically curable component (I) The photocationically curable component (I) is a component that imparts adhesive strength by polymerization curing due to irradiation with active energy rays, and preferably contains a first epoxy compound (I-1) described in detail below. The photocationically curable component (I) preferably further contains a second epoxy compound (I-2) or a third epoxy compound (I-3) described in detail below together with the first epoxy compound (I-1), and more preferably further contains at least a second epoxy compound (I-2) together with the first epoxy compound (I-1). The photocationically curable component (I) further preferably further contains a second epoxy compound (I-2) and a third epoxy compound (I-3) together with the first epoxy compound (I-1).

[0093] The photocurable adhesive preferably contains a photocationic polymerization initiator (II). This allows the photocationic curable component to be cured by cationic polymerization due to irradiation with active energy rays to form an adhesive layer. The photocationic polymerization initiator (II) generates cationic species or Lewis acids by irradiation with active energy rays such as visible light, ultraviolet light, X-rays, and electron beams, and initiates the polymerization reaction of the photocationic curable component. Since the photocationic polymerization initiator (II) acts catalytically with light, it has excellent storage stability and workability even when mixed with the photocationic curable component. Examples of compounds that generate cationic species or Lewis acids by irradiation with active energy rays and can be used as the photocationic polymerization initiator (II) include aromatic diazonium salts; onium salts such as aromatic iodonium salts and aromatic sulfonium salts; and iron-arene complexes.

[0094] Examples of aromatic diazonium salts include benzenediazonium hexafluoroantimonate, benzenediazonium hexafluorophosphate, and benzenediazonium hexafluoroborate.

[0095] Examples of aromatic iodonium salts include diphenyliodonium tetrakis(pentafluorophenyl)borate, diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, and di(4-nonylphenyl)iodonium hexafluorophosphate.

[0096] Examples of aromatic sulfonium salts include triphenylsulfonium hexafluorophosphate, triphenylsulfonium tetrakis(pentafluorophenyl)borate, 4,4-bis[diphenylsulfonio]diphenyl sulfide bishexafluorophosphate, 4,4-bis[di(β-hydroxyethoxy)phenylsulfonio]diphenyl sulfide bishexafluoroantimonate, 4,4-bis[di(β-hydroxyethoxy)phenylsulfonio]diphenyl sulfide bishexafluorophosphate, 7-[di(p-toluyl)sulfonio]-2-isopropylthioxanthone hexafluoroantimonate, 7-[di(p-toluyl)sulfonio]-2-isopropylthioxanthone tetrakis(pentafluorophenyl)borate, and 4-phenylcarbonyl-4-diphenylsulfonio-diphenyl sulfide. hexafluorophosphate, 4-(p-tert-butylphenylcarbonyl)-4-diphenylsulfonio-diphenylsulfide hexafluoroantimonate, 4-(p-tert-butylphenylcarbonyl)-4-di(p-toluyl)sulfonio-diphenylsulfide tetrakis(pentafluorophenyl)borate.

[0097] Examples of iron-arene complexes include xylene-cyclopentadienyliron(II) hexafluoroantimonate, cumene-cyclopentadienyliron(II) hexafluorophosphate, and xylene-cyclopentadienyliron(II) tris(trifluoromethylsulfonyl)methanide.

[0098] The photocationic polymerization initiator (II) may be used alone or in combination of two or more. Among the above, aromatic sulfonium salts are preferably used because they have ultraviolet absorption properties even in the wavelength region around 300 nm, and therefore can provide an adhesive layer having excellent curing properties, mechanical strength, and adhesive strength.

[0099] The content of the photocationic polymerization initiator (II) is preferably 1 to 10 parts by mass, more preferably 2 to 6 parts by mass, based on 100 parts by mass of the total photocationic curable component. By including 1 part by mass or more of the photocationic polymerization initiator (II), the photocationic curable component can be sufficiently cured, and the obtained polarizing plate can be given high mechanical strength and adhesive strength. On the other hand, if the content is too high, the ionic substance in the cured product increases, which increases the hygroscopicity of the cured product and may reduce the durability of the polarizing plate. Therefore, the content of the photocationic polymerization initiator (II) is preferably 10 parts by mass or less based on 100 parts by mass of the photocationic curable component. EXAMPLES

[0100] The present invention will now be described in detail with reference to examples, comparative examples, and reference examples, but the present invention is not limited to the following examples. The evaluation methods used in the present invention are as follows.

[0101] (1) Glass transition temperature In accordance with JIS K7121:2012, a 10 mg resin sample was heated at 20°C / min over the temperature range of 25 to 300°C using a differential scanning calorimeter (Seiko Instruments, DSC6200), and the extrapolated glass transition onset temperature obtained from the DSC curve was taken as the glass transition temperature.

[0102] (2) Number average molecular weight 0.03 g of polyester resin was dissolved in 10 ml of tetrahydrofuran, and the number average molecular weight was measured using a GPC-LALLS apparatus low-angle light scattering photometer LS-8000 (manufactured by Tosoh Corporation, tetrahydrofuran solvent, reference: polystyrene) at a column temperature of 30°C, a flow rate of 1 ml / min, and a column (Shodex KF-802, 804, 806, manufactured by Showa Denko K.K.).

[0103] (3) Polyester resin composition The polyester resin was dissolved in deuterated chloroform, and 1H-NMR analysis was carried out using a Varian Gemini-200 nuclear magnetic resonance analyzer (NMR), and the molar percentage ratio of each component was determined from the integral ratio.

[0104] (4) Acid value of polyester A polyester sample (1 g, solid content) was dissolved in 30 ml of chloroform or dimethylformamide and titrated with a 0.1 N ethanolic solution of potassium hydroxide using phenolphthalein as an indicator to determine the amount (mg) of KOH required to neutralize the carboxyl groups per 1 g of sample.

[0105] (5) Degree of saponification of polyvinyl alcohol The residual acetate group (mol%) of the polyvinyl alcohol resin was quantified using sodium hydroxide according to JIS K6726:1994, and the value was taken as the degree of saponification (mol%). The same sample was measured three times, and the average value was taken as the degree of saponification (mol%).

[0106] (6) Formation of polyvinyl alcohol (PVA) layer A polyvinyl alcohol aqueous solution (PVA117 manufactured by Kuraray) adjusted to a solid content concentration of 3% by mass was applied with a wire bar to the adhesive layer and coating layer surface of the polyester film described in the Examples and Comparative Examples below, so that the thickness of the polyvinyl alcohol resin layer after drying would be 200 nm, and then dried for 5 minutes at 80° C. A red dye was added to the polyvinyl alcohol aqueous solution used to facilitate evaluation.

[0107] (7) Polyvinyl alcohol (PVA) adhesion The PVA layer described in the above-mentioned section on the formation of the PVA layer was formed on the easy-adhesion layer and coating layer of the polyester film described in the Examples and Comparative Examples. The polyester film on which the PVA was formed was measured for adhesion between the PVA layer and the polyester film having the easy-adhesion layer and coating layer in accordance with the description in 8.5.1 of JIS K5400:1990.

[0108] Specifically, a cutter guide with a gap of 2 mm is used to make 100 grid-shaped cuts on the hard coat layer surface, penetrating the PVA layer and reaching the polyester film having the easy-adhesion layer and the coating layer. Next, cellophane adhesive tape (manufactured by Nichiban, No. 405; 24 mm wide) is attached to the grid-shaped cut surface and rubbed with an eraser to completely adhere it. After that, the cellophane adhesive tape is peeled vertically from the PVA layer surface of the polarizer protective film, and the number of squares peeled off from the PVA layer surface of the polarizer protective film is counted visually, and the adhesion between the hard coat layer and the polyester film having the easy-adhesion layer and the coating layer is calculated using the following formula. Note that the squares that are partially peeled off are also counted as peeled squares. PVA adhesion of 90(%) or more is considered to be acceptable. PVA adhesion (%) = {1-(number of peeled squares / 100)} x 100

[0109] (8) Formation of a photocurable adhesive layer A coating solution for forming a photocurable adhesive layer having the following composition was applied onto the easy-adhesion layer and coating layer of a polyester film described in the Examples and Comparative Examples described later, using a wire bar #3. Next, the film coated with the photocurable adhesive layer was irradiated with ultraviolet light of 500 mJ / cm2 using a high-pressure mercury lamp, to obtain a polarizer protective film having a photocurable adhesive layer with a thickness of 5 μm. Coating liquid for forming photocurable adhesive layer 3,4-Epoxycyclohexylmethyl-3,4'-epoxycyclohexanecarboxylate (Daicel Celloxide2021P) 23.81% by mass 1,4-Cyclohexanedimethanol diglycidyl ether (Nagase ChemteX EX-216L) 23.81% by mass 3-Ethyl-3-[(3-ethyloxetan-3-yl)methoxymethyl]oxetane (Aronoxetane DOX221 manufactured by Toagosei) 47.62% by mass Cationic Initiators (Sanapro CPI-100P) 4.76% by mass

[0110] (9) Adhesion of photocurable adhesives A photocurable adhesive layer was formed on the easy-adhesion layer and coating layer of the polyester film described in the Examples and Comparative Examples, as described in the above section on the formation of a photocurable adhesive layer. The polyester film having the easy-adhesion layer or coating layer on which the photocurable adhesive layer was formed was measured for adhesion to the photocurable adhesive layer in accordance with the description of 8.5.1 of JIS K5400:1990.

[0111] Specifically, a cutter guide with a gap of 2 mm is used to make 100 grid-like cuts on the photocurable adhesive layer surface, penetrating the photocurable adhesive layer and reaching the film. Next, cellophane adhesive tape (manufactured by Nichiban, No. 405; 24 mm wide) is attached to the grid-like cut surface and rubbed with an eraser to completely adhere it. After that, the cellophane adhesive tape is peeled vertically from the photocurable adhesive layer surface of the photocurable adhesive laminated polarizer protective film, and the number of squares peeled off from the photocurable adhesive layer surface is counted visually, and the adhesion between the photocurable adhesive layer and the film is calculated using the following formula. Note that the squares that are partially peeled off are also counted as peeled squares. The photocurable adhesive adhesion of 90(%) or more is considered to be acceptable. Photocurable adhesive adhesion (%) = {1-(number of peeled squares / 100)} x 100

[0112] (10) Peel strength after water adhesion The polyester film described in the Examples and Comparative Examples below is cut to 10 cm in the width direction and 1.5 cm in the length direction. A film 1.5 cm in the width direction and 1.5 cm in the length direction is overlapped on the end of the easy-adhesion layer surface or coating layer surface of the cut film. 0.03 g of water droplets are dropped onto the easy-adhesion layer surface or coating layer surface at the opposite end. Then, the easy-adhesion layer surface or coating layer surface of the film cut to 10 cm in the width direction and 1.5 cm in the length direction is overlapped, and the film is rolled evenly so that air does not enter from the side where the water droplets were dropped to the side where the film is overlapped. The sample is then placed in an oven at 50°C for 6 hours. For the removed sample, the 1.5 cm square film that had been sandwiched between the samples was removed, and the part that was not covered by water was used as the handle of the zipper. A peel test was then performed at room temperature in accordance with JIS K 6854-3:1999 using a tensile testing machine (Autograph, model number AGS-X, manufactured by Shimadzu Corporation), at a pulling speed of 0.3 m / min. The peel force (N / cm) was measured five times and the average was taken.

[0113] (11) Blocking resistance Cut each film into two pieces, each 3.5 cm square (3.5 cm long x 3.5 cm wide). Two sheets of each sample were stacked so that the adhesive layer surface or the coating layer surface of each sample was in contact with each other, and the film was left for one day in an environment of 30°C and 80% humidity with a pressure of 0.5 MPa applied in a direction perpendicular to the surface. The samples were then removed and the two samples were peeled off to evaluate the condition of each film. In the following Comparative Example 7, adhesion marks were observed and the two films were difficult to peel off, which was a poor result, but in the other Examples and Comparative Examples, the two films were peeled off without applying force and no adhesion marks were observed at all.

[0114] (12) Surface nitrogen element content measurement ESCA (X-ray photoelectron spectrometry) measurement The surface composition of the adhesive layer and coating layer of the polyester film described in the examples and comparative examples was measured by ESCA (Electron Spectroscopy for Chemical Analysis). The device used was K-Alpha+ (manufactured by Thermo Fisher Scientific). Details of the measurement conditions are as follows: The results are shown below. During the analysis, background was removed by the Shirley method. The surface nitrogen element content (at%) was calculated as the average value of the measurement results at three or more points. Measurement conditions Excitation X-ray: Monochromatic Al Kα line X-ray output: 12 kV, 6mA Photoelectron escape angle: 90 ° Spot size: 400μmφ Pass energy: 50eV Step: 0.1eV

[0115] (Polymerization of polyester resin) In a stainless steel autoclave equipped with a stirrer, a thermometer, and a partial reflux condenser, 194.2 parts by mass of dimethyl terephthalate, 184.5 parts by mass of dimethyl isophthalate, 14.8 parts by mass of dimethyl-5-sodium sulfoisophthalate, 233.5 parts by mass of diethylene glycol, 136.6 parts by mass of ethylene glycol, and 0.2 parts by mass of tetra-n-butyl titanate were charged, and an ester exchange reaction was carried out at a temperature of 160°C to 220°C for 4 hours. The temperature was then raised to 255°C, and the reaction system was gradually depressurized, and the reaction was carried out for 1 hour and 30 minutes under a reduced pressure of 30 Pa to obtain a copolymer polyester resin (A-1). The obtained copolymer polyester resin (A-1) was pale yellow and transparent. The reduced viscosity of the copolymer polyester resin (A-1) was measured and found to be 0.70 dl / g. The glass transition temperature measured by DSC was 40°C.

[0116] A copolymer polyester resin (A-2) having a different composition was obtained in the same manner. The compositions (mol % ratios) and other properties of these copolymer polyester resins measured by 1H-NMR are shown in Table 1.

[0117] A copolymer polyester resin (A-3) having a different composition was obtained in the same manner. The compositions (mol % ratios) and other properties of these copolymer polyester resins measured by 1H-NMR are shown in Table 1.

[0118] A copolymer polyester resin (A-4) having a different composition was obtained in the same manner. The compositions (mol % ratios) and other properties of these copolymer polyester resins measured by 1H-NMR are shown in Table 1.

[0119] A copolymer polyester resin (A-5) having a different composition was obtained in the same manner. The compositions (mol % ratios) and other properties of these copolymer polyester resins measured by 1H-NMR are shown in Table 1.

[0120] [Table 1]

[0121] (Preparation of Polyester Water Dispersion) In a reactor equipped with a stirrer, a thermometer and a reflux device, 15 parts by mass of polyester resin (A-1) and 15 parts by mass of ethylene glycol n-butyl ether were placed, heated at 110 ° C., and stirred to dissolve the resin. After the resin was completely dissolved, 70 parts by mass of water was gradually added to the polyester solution while stirring. After the addition, the liquid was cooled to room temperature while stirring to prepare a milky white polyester water dispersion (Aw-1) with a solid content of 15% by mass. Similarly, an aqueous dispersion was prepared using polyester resin (A-2) instead of polyester resin (A-1), and polyester water dispersion (Aw-2) was prepared. The same operation as for polyester resin (A-1) was performed for polyester resin (A-3), polyester resin (A-4) and polyester resin (A-5), and polyester water dispersion (Aw-3), polyester water dispersion (Aw-4) and polyester water dispersion (Aw-5) were prepared, respectively.

[0122] (Preparation of aqueous polyvinyl alcohol solution) 90 parts by mass of water was placed in a container equipped with a stirrer and a thermometer, and 10 parts by mass of polyvinyl alcohol resin (manufactured by Kuraray) (B-1) with a polymerization degree of 500 was gradually added while stirring. After addition, the liquid was heated to 95°C while stirring to dissolve the resin. After dissolution, the solution was cooled to room temperature while stirring to prepare an aqueous polyvinyl alcohol solution (Bw-1) with a solid content of 10% by mass. Similarly, an aqueous solution was prepared using polyvinyl alcohol resin (B-2) instead of polyvinyl alcohol resin (B-1), and each was named (Bw-2). The saponification degrees of polyvinyl alcohol resins (B-1) and (B-2) are shown in Table 2.

[0123] [Table 2]

[0124] (Polymerization of active methylene-blocked isocyanate crosslinking agents) A four-neck flask equipped with a stirrer, thermometer, reflux condenser, and nitrogen inlet was filled with nitrogen and charged with 1000 parts by mass of HDI and 22 parts by mass of trimethylolpropane (molecular weight 134), a trihydric alcohol. The temperature inside the reactor was kept at 90°C for 1 hour while stirring to carry out urethane formation. The temperature of the reaction liquid was then kept at 60°C, and the isocyanurate catalyst trimethylbenzylammonium hydroxide was added. When the conversion rate reached 48%, phosphoric acid was added to stop the reaction. The reaction liquid was then filtered and the unreacted HDI was removed using a thin-film distillation apparatus.

[0125] The viscosity of the obtained polyisocyanate at 25°C was 25,000 mPa s, the isocyanate group content was 19.9 mass%, the number average molecular weight was 1080, and the average number of isocyanate groups was 5.1. NMR measurement was then used to confirm the presence of urethane bonds, allophanate bonds, and isocyanurate bonds.

[0126] A four-neck flask equipped with a stirrer, a thermometer, a reflux condenser, a nitrogen inlet tube, and a dropping funnel was conditioned with nitrogen, and 100 parts by mass of the polyisocyanate obtained above, 42.3 parts by mass of methoxypolyethylene glycol having a number average molecular weight of 400, and 76.6 parts by mass of dipropylene glycol dimethyl ether were charged and maintained at 80° C. for 6 hours. Thereafter, the reaction temperature was cooled to 60° C., and 72 parts by mass of diethyl malonate and 0.88 parts by mass of a 28% methanol solution of sodium methylate were added, and the mixture was maintained for 4 hours, after which 0.86 parts by mass of 2-ethylhexyl acid phosphate was added.

[0127] Subsequently, 43.3 parts by mass of diisopropylamine was added, and the reaction liquid temperature was maintained at 70° C. for 5 hours. This reaction liquid was analyzed by gas chromatography to confirm that the reaction rate of diisopropylamine was 70%, and an active methylene-blocked isocyanate crosslinking agent (C-1) with a solid content concentration of 70% by mass was obtained.

[0128] (Polymerization of pyrazole-blocked isocyanate crosslinkers) In a flask equipped with a stirrer, a thermometer, and a reflux condenser, 65.02 parts by mass of a polyisocyanate compound having an isocyanurate structure made from hexamethylene diisocyanate (Asahi Kasei Chemicals, Duranate TPA) and 21.90 parts by mass of N-methylpyrrolidone were dissolved, and 29.15 parts by mass of 3,5-dimethylpyrazole (dissociation temperature: 120 ° C., boiling point: 218 ° C.) and 21.90 parts by mass of polyethylene glycol monomethyl ether having a number average molecular weight of 500 were added, and the mixture was kept at 70 ° C. for 2 hours under a nitrogen atmosphere. Then, 3.98 parts by mass of trimethylolpropane were dropped. After measuring the infrared spectrum of the reaction solution and confirming that the absorption of the isocyanate group had disappeared, 161.15 parts by mass of water was added to obtain a blocked polyisocyanate aqueous dispersion (C-2) with a solid content of 40% by mass. The number of functional groups of the blocked isocyanate crosslinking agent was 5.

[0129] (Polymerization of Oxime-Blocked Isocyanate Crosslinking Agent) A flask equipped with a stirrer, a thermometer, and a reflux condenser was charged with 100 parts by mass of a polyisocyanate compound having an isocyanurate structure made from hexamethylene diisocyanate (Asahi Kasei Chemicals, Duranate TPA), 55 parts by mass of propylene glycol monomethyl ether acetate, and 30 parts by mass of polyethylene glycol monomethyl ether (average molecular weight 750), and the mixture was kept at 70°C for 4 hours under a nitrogen atmosphere. The reaction liquid temperature was then lowered to 50°C, and 47 parts by mass of methyl ethyl ketoxime was added dropwise. The infrared spectrum of the reaction liquid was measured to confirm that the absorption of the isocyanate group had disappeared, and an oxime-blocked isocyanate crosslinking agent (C-3) with a solid content of 75% by mass was obtained.

[0130] (Polymerization of carbodiimide crosslinking agents) A flask equipped with a stirrer, a thermometer, and a reflux condenser was charged with 168 parts by mass of hexamethylene diisocyanate and 220 parts by mass of polyethylene glycol monomethyl ether (M400, average molecular weight 400), and stirred at 120 ° C for 1 hour. Further, 26 parts by mass of 4,4'-dicyclohexylmethane diisocyanate and 3.8 parts by mass of 3-methyl-1-phenyl-2-phosphorene-1-oxide (2% by mass relative to the total isocyanate) were added as a carbodiimide catalyst, and the mixture was stirred at 185 ° C for another 5 hours under a nitrogen stream. The infrared spectrum of the reaction solution was measured, and it was confirmed that the absorption at a wavelength of 2200 to 2300 cm-1 had disappeared. The mixture was allowed to cool to 60 ° C, and 567 parts by mass of ion-exchanged water was added to obtain a carbodiimide-based crosslinking agent (C-4) with a solid content of 40% by mass.

[0131] (Melamine-based crosslinking agent) As the melamine-based crosslinking agent, Amidea M-3 (solid content concentration 75%) manufactured by DIC Corporation was used (melamine-based crosslinking agent (C-5)).

[0132] (Polymerization of oxazoline-based crosslinking agents) A mixture of 58 parts by mass of ion-exchanged water and 58 parts by mass of isopropanol as an aqueous medium, and 4 parts by mass of a polymerization initiator (2,2'-azobis(2-amidinopropane) dihydrochloride) were placed in a flask equipped with a thermometer, a nitrogen gas inlet tube, a reflux condenser, a dropping funnel, and a stirrer. Meanwhile, a mixture of 16 parts by mass of 2-isopropenyl-2-oxazoline as a polymerizable unsaturated monomer having an oxazoline group, 32 parts by mass of methoxypolyethylene glycol acrylate (average number of moles of ethylene glycol added: 9 moles, Shin-Nakamura Chemical Co., Ltd.), and 32 parts by mass of methyl methacrylate were placed in the dropping funnel, and added dropwise at 70°C for 1 hour under a nitrogen atmosphere. After the dropwise addition was completed, the reaction solution was stirred for 9 hours and cooled to obtain a water-soluble resin (C-6) having an oxazoline group with a solid content of 40% by mass.

[0133] (Epoxy crosslinking agent) As the epoxy crosslinking agent, Denacol EX-521 (solid content concentration 100%) manufactured by Nagase ChemteX Corporation was used (epoxy crosslinking agent (C-7)).

[0134] (Polymerization of Bisulfite Blocked Isocyanate Crosslinker) 34 parts by mass of hexamethylene diisocyanate was added to 200 parts by mass of polyester of ethylene oxide adduct of bisphenol A and maleic acid, and the mixture was reacted, and 73 parts by mass of 30% by mass aqueous sodium bisulfite solution was added and stirred. The mixture was then diluted with water to obtain a bisulfite-blocked polyisocyanate compound (C-8).

[0135] Example 1 (1) Preparation of coating solution The following coating materials were mixed to prepare a coating solution with a solids ratio of polyester resin (A-1) / polyvinyl alcohol resin (B-1) / active methylene blocked isocyanate crosslinker (C-1) of 92 / 3 / 5. The polyester water dispersion used was an aqueous dispersion (Aw-1) in which a polyester resin with an acid value of 2 mgKOH / g was dispersed, and the polyvinyl alcohol aqueous solution used was an aqueous solution (Bw-1) in which polyvinyl alcohol with a saponification degree of 88 mol% was dissolved. Water 32.62% by mass Isopropanol 30.00% by mass Polyester water dispersion (Aw-1) 33.59% by mass Polyvinyl alcohol aqueous solution (Bw-1) 1.46% by mass Blocked isocyanate crosslinking agent (C-1) 0.40% by mass Particles 0.49% by mass (Silica sol with average particle size of 450 nm, solid content concentration of 4% by mass) Particles 1.29% by mass (Silica sol with average particle size of 40 nm, solid content concentration of 40% by mass) Surfactant: 0.15% by mass (Silicone-based, solids concentration 10% by weight)

[0136] (2) Manufacturing of highly adhesive polyester film As the raw polymer for the film, PET resin pellets having an intrinsic viscosity of 0.62 dl / g (solvent: phenol / tetrachloroethane = 60 / 40) and substantially free of particles were dried at 135°C for 6 hours under a reduced pressure of 133 Pa. Then, the pellets were fed to an extruder, melt-extruded into a sheet at about 280°C, and rapidly cooled and solidified on a rotating cooling metal roll maintained at a surface temperature of 20°C to obtain an unstretched PET sheet.

[0137] Next, the coating solution was applied to one side of a PET film by roll coating, and then dried at 90°C for 10 seconds. The final (stretched) coating thickness after drying was adjusted to 150 nm. The film was then stretched 4.0 times in the width direction at 100°C using a tenter, and heated at a heat setting temperature of 180°C for 6 seconds while the length of the film in the width direction was fixed, and then subjected to a 3% width direction relaxation treatment at 180°C for 6 seconds to obtain an easily adhesive polyester film having a thickness of 100 μm. The evaluation results are shown in Table 3.

[0138] The polyester film described above was evaluated for each of the above-mentioned items, and the results are shown in Table 3.

[0139] Example 2 The following coating materials were mixed, and an easily adhesive polyester film was obtained in the same manner as in Example 1, except that the solid content ratio of polyester resin (A-1) / polyvinyl alcohol resin (B-1) / active methylene blocked isocyanate crosslinking agent (C-1) was changed to 83 / 5 / 12. Water 33.75% by mass Isopropanol 30.40% by mass Polyester water dispersion (Aw-1) 30.34% by mass Polyvinyl alcohol aqueous solution (Bw-1) 2.67% by mass Blocked isocyanate crosslinking agent (C-1) 0.95% by mass Particles 0.49% by mass (Silica sol with average particle size of 450 nm, solid content concentration of 4% by mass) Particles 1.25% by mass (Silica sol with average particle size of 40 nm, solid content concentration of 40% by mass) Surfactant: 0.15% by mass (Silicone-based, solids concentration 10% by weight)

[0140] Example 3 An easily adhesive polyester film was obtained in the same manner as in Example 2, except that in the coating liquid, the polyester resin was changed to (A-2) and the polyester water dispersion was changed to (Aw-2).

[0141] Example 4 An easily adhesive polyester film was obtained in the same manner as in Example 1, except that the solid content ratio of the polyester resin (A-1) / polyvinyl alcohol resin (B-1) / active methylene blocked isocyanate crosslinking agent (C-1) in the coating solution was changed to 55 / 20 / 25.

[0142] Example 5 An easily adhesive polyester film was obtained in the same manner as in Example 4, except that in the coating liquid, the polyvinyl alcohol-based resin was changed to (B-2) and the aqueous polyvinyl alcohol solution was changed to (Bw-2).

[0143] Example 6 In the coating solution, the solid content ratio of polyester resin (A-1) / polyvinyl alcohol resin (B-1) / active methylene blocked isocyanate crosslinking agent (C-1) / carbodiimide crosslinking agent (C-4) was changed to 56 / 37 / 5 / 2, but the same procedure as in Example 1 was repeated to obtain an easily adhesive polyester film.

[0144] Example 7 In the coating solution, the solid content ratio of polyester resin (A-1) / polyvinyl alcohol resin (B-1) / active methylene blocked isocyanate crosslinking agent (C-1) / melamine crosslinking agent (C-5) was changed to 80 / 15 / 4 / 1, but the same procedure as in Example 1 was repeated to obtain an easily adhesive polyester film.

[0145] Example 8 In the coating solution, the solid content ratio of polyester resin (A-1) / polyvinyl alcohol resin (B-1) / active methylene blocked isocyanate crosslinking agent (C-1) / pyrazole blocked isocyanate crosslinking agent (C-2) was changed to 65 / 27 / 6 / 2, but the same procedure as in Example 1 was repeated to obtain an easily adhesive polyester film.

[0146] Example 9 In the coating solution, the solid content ratio of polyester resin (A-1) / polyvinyl alcohol resin (B-1) / active methylene blocked isocyanate crosslinking agent (C-1) / oxazoline crosslinking agent (C-6) was changed to 71 / 18 / 8 / 3, but the same procedure as in Example 1 was repeated to obtain an easily adhesive polyester film.

[0147] Example 10 An easily adhesive polyester film was obtained in the same manner as in Example 1, except that the solid content ratio of polyester resin (A-1) / polyvinyl alcohol resin (B-1) / active methylene blocked isocyanate crosslinking agent (C-1) in the coating solution was changed to 45 / 45 / 10.

[0148] Example 11 An easily adhesive polyester film was obtained in the same manner as in Example 1, except that the solid content ratio of polyester resin (A-1) / polyvinyl alcohol resin (B-1) / active methylene blocked isocyanate crosslinking agent (C-1) in the coating solution was changed to 40 / 30 / 30.

[0149] Example 12 An easily adhesive polyester film was obtained in the same manner as in Example 1, except that the solid content ratio of polyester resin (A-1) / polyvinyl alcohol resin (B-1) / active methylene blocked isocyanate crosslinking agent (C-1) in the coating solution was changed to 25 / 65 / 10.

[0150] Example 13 The following coating materials were mixed, and an easily adhesive polyester film was obtained in the same manner as in Example 1, except that the solid content ratio of polyester resin (A-1) / polyvinyl alcohol resin (B-1) / melamine crosslinking agent (C-5) / pyrazole blocked isocyanate crosslinking agent (C-2) was changed to 25 / 65 / 8 / 2. Water 17.50% by mass Isopropanol 30.00% by mass Polyester water dispersion (Aw-1) 8.91% by mass Polyvinyl alcohol aqueous solution (Bw-1) 34.67% by mass Blocked isocyanate crosslinking agent (C-2) 0.27% by mass Melamine crosslinker (C-5) 0.71% by mass Particles 0.49% by mass (Silica sol with average particle size of 450 nm, solid content concentration of 4% by mass) Particles 1.25% by mass (Silica sol with average particle size of 40 nm, solid content concentration of 40% by mass) Surfactant: 0.15% by mass (Silicone-based, solids concentration 10% by weight) p-Toluenesulfonic acid 0.06% by mass

[0151] Example 14 An easily adhesive polyester film was obtained in the same manner as in Example 1, except that the solid content ratio of polyester resin (A-3) / polyvinyl alcohol resin (B-1) / pyrazole blocked isocyanate crosslinking agent (C-2) in the coating solution was changed to 85 / 5 / 10.

[0152] Example 15 An easily adhesive polyester film was obtained in the same manner as in Example 1, except that the solid content ratio of polyester resin (A-4) / polyvinyl alcohol resin (B-1) / pyrazole blocked isocyanate crosslinking agent (C-2) in the coating solution was changed to 85 / 5 / 10.

[0153] Example 16 An easily adhesive polyester film was obtained in the same manner as in Example 1, except that the solid content ratio of polyester resin (A-5) / polyvinyl alcohol resin (B-1) / active methylene blocked isocyanate crosslinking agent (C-1) in the coating solution was changed to 85 / 5 / 10.

[0154] Comparative Example 1 A polyester film having a coating layer was obtained in the same manner as in Example 1, except that the composition of the coating solution was changed as follows. Water 28.66% by mass Isopropanol 30.00% by mass Polyester water dispersion (Aw-1) 27.49% by mass Polyvinyl alcohol aqueous solution (Bw-1) 10.85% by mass Oxime-blocked isocyanate crosslinker (C-3) 0.29% by mass Particles 0.49% by mass (Silica sol with average particle size of 450 nm, solid content concentration of 4% by mass) Particles 1.59% by mass (Silica sol with average particle size of 40 nm, solid content concentration of 40% by mass) Surfactant: 0.15% by mass (Silicone-based, solids concentration 10% by weight) catalyst (Organotin compounds, solid content 10% by mass) 0.48% by mass

[0155] Comparative Example 2 A polyester film having a coating layer was obtained in the same manner as in Example 1, except that the solid content ratio of the polyester resin (A-1) / polyvinyl alcohol resin (B-1) / active methylene blocked isocyanate crosslinking agent (C-1) in the coating solution was changed to 30 / 5 / 65.

[0156] Comparative Example 3 A polyester film having a coating layer was obtained in the same manner as in Example 1, except that the solid content ratio of the polyester resin (A-1) / polyvinyl alcohol resin (B-1) / active methylene blocked isocyanate crosslinking agent (C-1) in the coating solution was changed to 45 / 15 / 40.

[0157] Comparative Example 4 A polyester film having a coating layer was obtained in the same manner as in Example 1, except that the solid content ratio of the polyester resin (A-1) / polyvinyl alcohol resin (B-1) / active methylene blocked isocyanate crosslinking agent (C-1) in the coating solution was changed to 95 / 0 / 5.

[0158] Comparative Example 5 In the coating solution, the solid content ratio of polyester resin (A-1) / polyvinyl alcohol resin (B-1) / active methylene blocked isocyanate crosslinking agent (C-1) was changed to 45 / 45 / 10, and the heat setting temperature and relaxation treatment temperature in the production of the highly adhesive polyester film were changed from 180°C to 160°C. Except for this, a polyester film having a coating layer was obtained in the same manner as in Example 1.

[0159] Comparative Example 6 In the coating solution, the blocked isocyanate crosslinking agent was changed to an epoxy-based crosslinking agent (C-7), and the solid content ratio of polyester-based resin (A-1) / polyvinyl alcohol-based resin (B-1) / epoxy-based crosslinking agent (C-7) was changed to 45 / 42 / 13. Except for this, a polyester film having a coating layer was obtained in the same manner as in Example 1.

[0160] Comparative Example 7 A polyester film having a coating layer was obtained in the same manner as in Example 1, except that the solid content ratio of the polyester resin (A-1) / polyvinyl alcohol resin (B-1) / active methylene blocked isocyanate crosslinking agent (C-1) in the coating solution was changed to 50 / 50 / 0.

[0161] Comparative Example 8 In the coating solution, the solid content ratio of polyester resin (A-1) / polyvinyl alcohol resin (B-1) / active methylene blocked isocyanate crosslinking agent (C-1) was changed to 92 / 3 / 5, and the drying temperature and time in the production of the highly adhesive polyester film were changed from 90°C for 10 seconds to 70°C for 20 seconds. Except for this, a polyester film having a coating layer was obtained in the same manner as in Example 1.

[0162] Comparative Example 9 A polyester film having a coating layer was obtained in the same manner as in Example 1, except that the composition of the coating solution was changed as follows. Water 12.70% by mass Isopropanol 30.00% by mass Polyester water dispersion (Aw-1) 29.17% by mass Polyvinyl alcohol aqueous solution (Bw-1) 21.90% by mass Blocked isocyanate crosslinking agent (C-1) 1.00% by mass Blocked isocyanate (C-8) 2.70% by mass Particles 1.80% by mass (Silica sol with average particle size of 40 nm, solid content concentration of 40% by mass) Surfactant: 0.10% by mass (Silicone-based, solids concentration 100% by mass) catalyst (Organotin compounds, solid content concentration 10% by mass) 0.60% by mass Sodium bicarbonate 0.01% by mass Sodium carbonate monohydrate 0.02% by mass

[0163] [Table 3] [Industrial Applicability]

[0164] According to the present invention, it has become possible to provide a highly adhesive polyester film which not only exhibits excellent adhesion to a polarizer, but also exhibits excellent adhesion to both hydrophilic adhesives and photocurable adhesives used to bond a polarizer and a polarizer protective film, and which does not require a catalyst and has excellent environmental compatibility, making it suitable for optical applications, particularly for use as a polarizer protective film.

Claims

1. A polyester film having an easy-adhesion layer on at least one surface, the easy-adhesion layer is formed by curing a composition containing a polyester resin, a polyvinyl alcohol resin, and a crosslinking agent having a nitrogen element, The polyester resin has a glass transition temperature of more than 90° C. and not more than 140° C. The adhesive layer is substantially free of organotin as a curing catalyst for the composition, The nitrogen element content of the surface constituent elements of the easy-adhesion layer surface, as analyzed by ESCA (X-ray photoelectron spectroscopy), is 2.0 at% or more and 3.0 at% or less. Highly adhesive polyester film.

2. 2. The highly adhesive polyester film according to claim 1, wherein the peel strength of the highly adhesive layer after adhesion of water is 2 N / cm or less.

3. 3. The highly adhesive polyester film according to claim 1, which is used as a polarizer protective film.

Citation Information

Patent Citations

  • Polarizing plate, its manufacturing method, optical member, and liquid crystal display device

    JP2004245925A

  • Polyester resin molding film

    JP2013027994A

  • Laminated polyester film

    JP2013063610A

  • Optical film

    JP2013231785A

  • Polarizer protective acrylic film, polarizing plate, and liquid crystal display device

    JP2014035411A